PENGUATAN MODERASI BERAGAMA DENGAN KEGIATAN RUTIN PEMBACAAN SHALAWAT DIBA’ AL-BARZANJI OLEH MUSLIMAT NU JAMAAH MASJID BAITUL MUTTAQIN DESA PURWOASRI - Faiqotul Hikmah, Sofi; Nur Kholiq, Ilham (Proceedings of Annual Conference on Community Engagement, 2023)
The focus of this service is to innovate the prayer reading activity in Ba’ al-Barzanji with new prayers that have never been read in this activity. This activity has been around since 1989. This activity can be called a recommended religious ritual because several propositions from the Koran encourage someone to recite shalawat because there are many blessings in it. Religion consists of belief, ritual and social, all three of which are found in the routine activity of reciting prayers at al-barzanji carried out by Muslim women from the congregation of the Baitul Muttaqin Mosque. Moderation in spiritual worship means not excessively raising one’s voice, not forbidding things that are permitted in the Koran, and this activity shows moderation between belief, ritual and social, because these three aspects are found in the activity of reciting prayers at the altar. ’ al-barzanji.